2022
DOI: 10.1101/2022.06.08.495100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved reduction of m6A marks during aging and neurodegeneration is linked to altered translation of synaptic transcripts

Abstract: N6-methyladenosine (m6A) plays diverse roles in the regulation of mRNA metabolism. In the mammalian brain it has been linked to developmental processes and memory function. However, the precise role of m6A in the context synaptic plasticity and especially during impaired cognition are not fully understood. Here, we describe the mouse and human brain m6A epi-transcriptome in a tissue-specific manner. We furthermore show that m6A levels undergo a massive decrease across mouse brain regions as a consequence of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…The research has shown the possibility of the existence of complex senescence regulatory mechanisms including RNA modifications (Sobieszczuk-Nowicka et al, 2018); therefore, investigation of the epigenetic mechanisms participating in leaf senescence is an important research topic. As has already been mentioned the role of m 6 A modifications in the aging of animal models as well as cell senescence has been previously reported (Castro-Hernańdez et al, 2022;Sun et al, 2022b). Recent findings about m 6 A modification in the process of aging include the participation of this modification in cell senescence, inflammation, autophagy, DNA damage, oxidative stress, neurodegenerative diseases, tumors, diabetes, and cardiovascular diseases.…”
mentioning
confidence: 75%
“…The research has shown the possibility of the existence of complex senescence regulatory mechanisms including RNA modifications (Sobieszczuk-Nowicka et al, 2018); therefore, investigation of the epigenetic mechanisms participating in leaf senescence is an important research topic. As has already been mentioned the role of m 6 A modifications in the aging of animal models as well as cell senescence has been previously reported (Castro-Hernańdez et al, 2022;Sun et al, 2022b). Recent findings about m 6 A modification in the process of aging include the participation of this modification in cell senescence, inflammation, autophagy, DNA damage, oxidative stress, neurodegenerative diseases, tumors, diabetes, and cardiovascular diseases.…”
mentioning
confidence: 75%